Customer experience perspective in majapahit house management in Bejijong Village, Mojokerto - Christanto, Gunawan; Andajani, Erna (Journal of Management and Business, 2021)
This study aims to explore the perspective of customer experience in managing Majapahit House in Bejijong Village by explaining the phenomena that are being the questions of the study. Then to explain the phenomena that occur, this study uses a qualitative method with a phenomenological paradigm. The results of this study indicate the views of managers and tourists towards activities that refer to three conditions: before, during the service delivery process and the service has been provided. This research is useful for business managers, especially related to the field of tourism to see the importance of managing customer experience.